Antioxidant Activities and Antioxidant Cream Formulation of Corn Silk (Zea Mays L) Extract - Safitri, Fifia Wulan; Syahreza, Ardhan; H., Siti Farah; Satrio B, M. Cahyo; Sulistyaningrum, Indriayati Hadi (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2016)
Introduction : One of the free radicals that can damage facial skin is coming from UV radiation of the sun. Free radicals are the main factors that can accelerate the early aging process. The administration of antioxidants are believed to increase immune system of the body especially to prevent skin aging.Objectives: to determine the antioxidant activity of the corn silk extract and cream formulation. Methods: Corn silk were extracted by maceration using 80% ethanol for 5 days. Determination of antioxidant activity was conducted using 2,2-diphenil 1-pichylhydazyl (DPPH). Optimization of the preparation formula using expert design by varying the concentration of tween 80 and spam 80. The evaluation of cream preparation included homogeneity, organoleptic, pH, adhesion, dispersive power and power irritation to the skin.Results: IC50 corn silk extract were obtained 30,03 ppm with AAI(antioxidant activity index) values of 3,33 ppm. From the results of evaluation of 8 formula indicates a homogenous cream preparation, evaluation of the organoleptic have a brownish-white color and does not become rancid, pH 6.5, adhesion range of 0.12 to 0.5 seconds, dispersive power from 5.1 to 7.3 cm and power irritation of the skin that show the results slightly irritating. Formula optimum dosage creams containing extracts of corn silk 0.0315%; propylene glycol 2.1%; 4.5% tween 80; Span 80 5.5%; sorbitol 20%; 5% stearic acid; VCO 20%; citric acid 0.7%; ascorbic acid 0.06%; Triethanolamine 2.45%; methyl paraben 0.25%; propyl paraben 0.15% and add distilled water 100ml.Conclusion: Corn silk extract (Zea mays L) has a very strong antioxidant activity and for the optimum cream formulation has comparison between emulsifier tween 80 and span 80 is 4.5% to 5.5%.